Determinants of muscle strength - Martin, L. (1997)
Determinants of Muscle Function : - PHYSIQUE - BODY COMPOSITION - BODY FAT - LEAN BODY MASS - ENERGY SYSTEMS - AEROBIC GLYCOLYSIS - STRENGTH - BODY COMPOSITION CHANGES - WITH STRENGTH GAIN - HYPERTROPHY - TRAINABILITY